Odpowiedź :
a)
10x2+15x-35+25x2+6x-4=35x2+21x-39
b)
(2x3+3x-7)*(-5x3-3x+2)=-10x6-6x4+3x3-15x4-9x2+6x+35x3+21x-14=
=10x6-21x4+38x3-9x2+27x-14
10x2+15x-35+25x2+6x-4=35x2+21x-39
b)
(2x3+3x-7)*(-5x3-3x+2)=-10x6-6x4+3x3-15x4-9x2+6x+35x3+21x-14=
=10x6-21x4+38x3-9x2+27x-14
a)=5*(2x³+3x-7)-2*(-5x³-3x+2)=10x³+15x-35-(-10x³-6x+4)=10x³+15x-35+10x³+6x-4=20x³+21x-39
b)=(2x³+3x-7)*(-5x³-3x+2)=-10x⁶-6x⁴+4x³-15x⁴-9x²+6x+35x³+21x-14=-10x⁶-21x⁴+39x³-9x²+27x-14
b)=(2x³+3x-7)*(-5x³-3x+2)=-10x⁶-6x⁴+4x³-15x⁴-9x²+6x+35x³+21x-14=-10x⁶-21x⁴+39x³-9x²+27x-14